2010
DOI: 10.1093/geront/gnq040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telephone Support Groups on Costs of Care for Veterans With Dementia

Abstract: The TEP caregiver intervention resulted in short-term cost savings for veteran care recipients. Future studies of caregiver interventions should examine their effects on costs of care for the care recipients in addition to their effects on caregiver outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 25 publications
0
78
0
Order By: Relevance
“…Our study was powered to detect small to moderate differences in change in cost, on the order of those observed by Wray et al 25 Further work with substantially larger samples could help to determine whether the small cost differences we observed exist.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our study was powered to detect small to moderate differences in change in cost, on the order of those observed by Wray et al 25 Further work with substantially larger samples could help to determine whether the small cost differences we observed exist.…”
Section: Discussionmentioning
confidence: 89%
“…We incorporated an indicator of veteran priority levels to help control for the impact of service priority on change in VHA cost. Wray et al 25 concluded that Medicare use in their study by veterans with dementia was minimal compared to VHA use among the same group of veterans. However, without measures of non-VHA health care use, we cannot determine whether PDC affected VHA care and non-VHA care access differentially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the VISN 2 population, the veterans whose caregivers participated in the telephone support and education program have been shown to have significantly decreased healthcare costs compared with veterans receiving usual care. 32 It may be challenging to implement similar programs outside the VA system where EMR technology is more limited, if available, and may not contain all the patient information available within the VA system. Conversely, Medicare now requires annual assessment for cognitive impairment, 42 and community practices that accept Medicare patients will soon need to develop strategies to attend to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include psychiatry 133 (including depression [134][135][136] and dementia 137 ), dermatology, [138][139][140][141][142][143][144] sleep apnea, 145 The following analysis is based on 14 cost studies ( Table 4) dealing with one or more of the target chronic diseases in this article and is organized on the basis of the particular cost method used in the study.…”
Section: Cost Studiesmentioning
confidence: 99%